2022
DOI: 10.24071/llt.v25i1.4485
|View full text |Cite
|
Sign up to set email alerts
|

Gazing at ‘The-You-Know-Who/What’ in Whatsapp: Deixis Used in Online Learning Amid Covid-19 Pandemic

Abstract: WhatsApp, as one of the most powerful and ubiquitous social media platforms, has become one of the promising tools utilized for English online learning during the current crisis, COVID-19 pandemic. Nevertheless, interacting effectively via this platform might be challenging for messages communicated to this platform might have more than one meaning that is likely to result in misunderstanding among the users. Thus, understanding deixis, known as one of the interactional phenomena in which language and context … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
2
3
0
1
Order By: Relevance
“…By using such temporal deixis, Kim Namjoon effectively guides his audience through his narrative, ensuring that they can follow and relate to his personal journey and experiences. It is worth noting that the relatively lower prevalence of temporal deixis in Kim Namjoon's speech aligns with the findings of previous research by Sugianto & Muslim (2022). Their research also pointed to a lower frequency of E-ISSN: 3026-569X; P-ISSN: 3026-734X Journal Homepage: http://journal.lontaradigitech.com/GLENS temporal deixis in comparison to other deixis types.…”
Section: Findings and Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…By using such temporal deixis, Kim Namjoon effectively guides his audience through his narrative, ensuring that they can follow and relate to his personal journey and experiences. It is worth noting that the relatively lower prevalence of temporal deixis in Kim Namjoon's speech aligns with the findings of previous research by Sugianto & Muslim (2022). Their research also pointed to a lower frequency of E-ISSN: 3026-569X; P-ISSN: 3026-734X Journal Homepage: http://journal.lontaradigitech.com/GLENS temporal deixis in comparison to other deixis types.…”
Section: Findings and Discussionsupporting
confidence: 86%
“…Upon scrutinizing the data, the researcher identified a total of 196 deixis instances, categorized as follows: 129 (65.8%) were personal deixis, 15 (7.7%) were spatial deixis, 10 (5.1%) were temporal deixis, 31 (15.8%) were discourse deixis, and 11 (5.6%) were social deixis. This observation aligns with the findings of Sugianto & Muslim (2022). The analysis of the text was conducted using the deixis theory proposed by Stephen C. Levinson, which encompasses five deixis types: person, time, place, social, and discourse deixis.…”
Section: Findings and Discussionsupporting
confidence: 78%
“…They also used different methods of data collection and analysis and also obtained varying results. For example, some erudite investigated indexical studies on social media such as WhatsApp (Sugianto & Muslim, 2022;Fuh, 2022) and platforms such as YouTube (Makarim, 2021) and Twitter (Squires, 2014). While the study of Sugianto and Muslim (2022) revealed that personal deixis was the most frequently used followed by social, discourse, place and time, Makarim's (2021) study showed that the deictic expressions of person, temporal, and spatial were applied in the advertisement of public transportation's YouTube video.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, some erudite investigated indexical studies on social media such as WhatsApp (Sugianto & Muslim, 2022;Fuh, 2022) and platforms such as YouTube (Makarim, 2021) and Twitter (Squires, 2014). While the study of Sugianto and Muslim (2022) revealed that personal deixis was the most frequently used followed by social, discourse, place and time, Makarim's (2021) study showed that the deictic expressions of person, temporal, and spatial were applied in the advertisement of public transportation's YouTube video. Fuh, (2022) posits that there were three types of indexical expressions used on social media during the Anglophone crisis namely person, time and place.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, written discourse can lead to misunderstandings, although the actual messages are understood [1,2]. The language used and the style of writing can affect the intended meaning or reaction of the recipients [3]. This highlights the complexity of written discourses in disseminating intended meanings and connecting with the recipients.…”
Section: Introductionmentioning
confidence: 99%